A Novel Approach for Spreading Dynamics of Polymer Fluids - Schubert, Dirk W.; Härth, Michael (9th Annual European Rheology Conference, 2014)

Elongational Flow Properties of Long-Chain Branched Poly(Ethylene Terephthalate) - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Polychar 22nd, 2014)

Elongational Flow Properties Of Long-Chain Branched Poly(Ethylene Terephthalate) - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (9th Annual European Rheology Conference, 2014)

Enhancing the electronic properties of VLS-grown silicon nanowires by surface charge transfer - Shalabny, Awad; Buonocore, Francesco; Celino, Massimo; Zhang, Lu; Sardashti, Kasra; Härth, Michael; Schubert, Dirk W.; Bashouti, Muhammad Y. (Applied Surface Science, 2022)
The need to develop new energy storage technology has led to deeper investigation into materials science to produce highly efficient batteries, primarily the lithium ion battery. The importance of electrodes in such devices has led to the reemergence of silicon nanowires (Si NWs) at the forefront of materials study—in this context, as an energy storage material (as electrodes). Redox potential and work function play the most important roles in charge transfer, the battery charging/discharging process. Thus, the NWs’ interfacial properties become important in achieving higher stability and efficiency. In this work, a deep study was conducted using equilibrium perturbation to change the surface electronic properties of Si NWs, which can be integrated into various technologies, while simultaneously achieving an interesting interface that is chemically passive and cheap to produce. By using an X-ray photoelectron spectroscope, a Kelvin probe, and contact angle measurement, combined with theoretical analysis, a full picture is achieved regarding the Si NWs’ interface, paving the way for this new technique to develop unique interfaces and to achieve a higher energy capacity and a longer lifetime.<br
Keywords: Non-equilibrium reactions; Silicon nanowire; Surface chemistry; Surface Fermi level; Sub-oxides; DFT; Work function; Charge transfer

Film blowing of linear and long-chain branched poly(ethylene terephthalate) - Härth, Michael; Dörnhöfer, Andrea (Polymers, 2020)
Film blowing of Poly(ethylene terephthalate) (PET) is challenging due its inherently low melt viscosity and poor melt strength. In this study, it is shown how the rheological properties of a commercial PET can be altered by reactive extrusion using either pyromellitic dianhydride (PMDA) or a multifunctional epoxy (Joncryl® ADR 4368) as chain extender, in order to improve the processing behavior during film blowing. The modified materials were characterized by shear and elongation rheometry and relevant processing characteristics, like melt pressure, bubble stability, and film thickness uniformity, were used to assess the influence of the type of modifier on processing and product performance. It is shown that PMDA is useful to increase the melt strength which leads to an improved bubble stability, while epoxy modified PET shows a reduced drawability that can cause problems at high take-up ratios. On the other hand, the epoxy modifier indicates a pronounced strain hardening during elongational deformation, and therefore leads to a better film thickness uniformity compared to the neat PET and the PET modified with PMDA. The differences with respect to processing performance are discussed and ascribed to the molecular structure of the materials.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Chain extender; Extensional viscosity; Film blowing; Film uniformity; Long-chain branches; Poly(ethylene terephthalate); Rheology

Influence of Residence Time and Moisture Content on Molar Mass Dispersity of Polyethylene Terepthalate - Härth, Michael; Lanyi, Franz; Schubert, Dirk W. (Abstracts, 2012)

Kinetics of molar mass build-up and degradation in a Polyethylene terephthalate melt - Härth, Michael; Schubert, Dirk W. (8th Annual European Rheology Conference, 2013)

Kinetics of Molar Mass Build-Up and Degradation in a Polyethylene Terephthalate Melt - Härth, Michael; Schubert, Dirk W. (29th International Conference of the Polymer Processing Society, 2013)

Master Curves for Spreading Dynamics of Polymer Fluids, Polymeric Materials - Härth, Michael; Schubert, Dirk W. (Abstracts, 2012)

Master Curves for Spreading Dynamics of Polymeric Fluids - Härth, Michael; Schubert, Dirk W. (Book of Abstracts, 2013)

Molecular structure and rheological properties of a poly(ethylene terephthalate) modified by two different chain extenders - Härth, Michael; Dörnhöfer, Andrea; Kaschta, Joachim; Münstedt, Helmut; Schubert, Dirk W. (Journal of Applied Polymer Science, 2020)
This paper compares the molecular structure and rheological properties of a commercial poly(ethylene terephthalate) (PET) after reactive processing with different concentrations of either pyromellitic dianhydride (PMDA) or a multifunctional epoxide (Joncryl®ADR‐4368) as a chain extender. By size exclusion chromatography with triple detection, an increase of molar mass, a broadening of molar mass distribution, and the generation of long‐chain branched molecules were found for both chain extenders. While gel‐free materials were obtained with PMDA, the processing with Joncryl leads to the formation of gels. The effect of branching, indicated by the Mark–Houwink exponent, is more pronounced for materials with Joncryl compared to PMDA and points to a more compact branching structure of the PET/Joncryl molecules. Rheological measurements in shear and elongation support the analysis from SEC and reveal a complex tree‐like branching structure for both chain extenders. In addition, the role of the two modifiers with respect to processing was assessed.<br

Novel results on spreading dynamics from theoretical and practical point of view - Schubert, Dirk W.; Härth, Michael (Book of Abstracts, 2011)

Ressourcenschonende Verpackungen aus PET durch reaktive Extrusion mit niedermolekularen Substanzen - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Würzburger Tage 2014, 2014)

Rheological study of the reaction kinetics in a poly(ethylene terephthalate) melt - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Polymer Degradation and Stability, 2015)
Time dependent measurements of the zero shear viscosity are applied to study the thermal stability of a commercial poly(ethylene terephthalate). Firstly, the factors influencing the experimental results, like moisture content and type of atmosphere (air or nitrogen) are briefly reviewed. Secondly, the time dependent viscosity is studied on dry samples in nitrogen atmosphere at various temperatures, as these conditions are commonly used for the rheological material characterization. All viscosity curves show a characteristic maximum which strongly depends on time and temperature. This maximum reflects the changes in molar mass resulting from the various chemical reactions. A simplified kinetic model, based on one build-up and one degradation reaction, is derived and used to analyze the experimental data. This model enables to determine the activation energy of flow (65 kJ mol(-1)) and the activation energy resulting from the temperature dependence of the molar mass maximum (120 kJ mol(-1)). Kinetic constants and corresponding activation energies of the chemical reactions are determined as well. The comparison with literature shows that the activation energies are similar to those found for the polymerization process. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Poly(ethylene terephthalate); Rheology; Reaction kinetics; Thermal degradation; Activation energy

Rheological Study on the Molar Mass Build-Up and Degradation in a PET Melt - Härth, Michael; Schubert, Dirk W. (Polychar 21st, 2013)

Shear and Elongational Flow Properties of Long-Chain Branched Poly(ethylene terephthalates) and Correlations to Their Molecular Structure - Härth, Michael; Kaschta, Joachim; Schubert, Dirk W. (Macromolecules, 2014)
Reactive processing with low-molar-mass modifiers is a well-known method to create long-chain branched (LCB) structures in a poly(ethylene terephthalate) (PET) melt. However, less is known about the elongational flow properties of LCB-PET. Therefore, the aim of this contribution is (a) to generate LCB molecules and (b) to evaluate the influence of the branching level on the transient elongational behavior. For this purpose, a commercial, linear PET and different contents (0.1-0.3 wt %) of the tetrafunctional modifier pyromellitic dianhydride (PMDA) were reactively processed. All samples were analyzed by size exclusion chromatography coupled with a light scattering device and characterized by shear and elongational rheometry. It was found that the molar mass distribution of the modified materials exhibit a high molar mass shoulder, leading to an increase of the weight-average molar mass and a broadening of the molar mass distribution. Moreover, the Mark-Houwink plot of the modified materials displays deviations from the power law toward lower intrinsic viscosities, which indicate the existence of LCB molecules. The shear viscosity shows a pronounced shear thinning behavior and a remarkable increase at low frequencies compared to the linear PET. Considering the transient elongational viscosity, a distinguished strain hardening is observed, which increases with increasing PMDA content and with increasing strain rate. From the results of the rheological and molecular characterization and by considering the chemical reaction mechanisms, it can be concluded that the PET modified with high PMDA contents has a treelike branch-on-branch architecture, which is well-known from low-density polyethylene melts.

Simple Approach for Spreading Dynamics of Polymeric Fluids - Härth, Michael; Schubert, Dirk W. (Macromolecular Chemistry and Physics, 2012)
The spreading of an axisymmetric drop on partially and completely wetted substrates is investigated from the theoretical and experimental point of view. In particular, novel physical models considering the capillary force, the gravitational force, and a viscous friction force simultaneously are derived. The models enable the analytical mathematical description of the drop radius as a function of the spreading time, which is useful for practical applications. Moreover, the construction of a master curve for the partial wetting scenario is proposed. The theoretical models are experimentally verified, using different polymer films as substrates and polydimethylsiloxanes of different viscosities as liquids. The comparison shows that theory and experiment are consistent.
Keywords: drop spreading; fluoropolymers; gravitational and capillary force; modelling; slicon oil

Simple approximate solution for modeling the spreading of a drop in the partial wetting case - Härth, Michael; Schubert, Dirk W. (Book of Abstracts, 2012)

Spreading Dynamics of Polymeric Fluids - Schubert, Dirk W.; Härth, Michael (Final Program and Book of Abstracts, 2011)
Spreading of fluids plays a key role in many processes and in research & development. For example, in the lubrication industry, he lubricating oil is evaluated by its spreading kinetic of a respective drop on a plane test surface. The time scale of the spreading dynamics depends not only on the interfacial tensions and the viscosity but also on the volume of the spreading fluid. For total and partial wetting scenarios novel models are developed from physical principals to describe the spreading kinetics detailed and consider gravity, interfacial energies and viscose friction simultaneosly. From mathematical perturbation calculations useful equations are derived [1] for practical application, like the following on

Spreading Kinetics on Completely Wettable Surface – Transition from Spherical Cap to Pancakes Shape - Albrecht, Michael; Härth, Michael; Schubert, Dirk W. (Abstracts, 2012)

Structural Analysis of Chain Extended Poly(ethylene terephthalate) from Rheological Data - Härth, Michael; Majewski, Jürgen; Schubert, Dirk W. (13th Bayreuth Polymer Symposium, 2013)